Choice of optimal search of module of integration of project data of computer-aided design engine - Синєглазов, В.М.; Кєворков, С.Г.; Кадем, Раад Карім (Proceedings of National Aviation University (archive), 2010)
Researches of forming of CAD system metamodels and its components design are conducted.